VARAITION IN LIFE HISTORY TRAITS IN FEW MEMBERS OF IMMIGRANS SPECIES GROUP OF DROSOPHILA EXPOSED TO LIGHT AND DARK CYCLE - B. P. HARINI (The Bioscan, 2011)
Over the last few decades Drosophila has developed as a model for the study of adaptation to environmental stress responses and much progress has been achieved. All organisms are strongly affected by their surrounding environment and the environmental factors play an important part in shaping ecology and evolution of biological systems. The present study is aimed to address the exposure of the closely related immigrans species group of Drosophila to variable biological rythms to ascertain its effect on life history traits. Interestingly, observation reveals that either reared at any stress conditions, the increase in copulation duration has resulted with increased productivity The developmental plasticity clearly involves acclimation of life history traits with the prevailing environment. While, exposure of the flies to dark regimes seems to be stressful environment and experienced reduction in reproductive potentiality by Drosophila populations under laboratory conditions.